POSTOPERATORY RECOVERY OF PATIENTS WITH HUMERUS FRACTURE THROUGH KINETIC PROCEDURES - Benedek Florian (Editura Univeristatii "Stefan cel Mare" din Suceava, 2021)
A trauma is needed to produce a humerus fracture, such as: accidents, falls, strong impact, overload. The most common symptoms in humerus fracture and which need to be analyzed are: pain, edema, bruising. Humerus fractures are diagnosed in most cases based on physical examination and a bone x-ray [2,5,11,13]. In this study, we began from the hypothesis that by using kinetic means, the patient with humeral fracture can be recovered in the best conditions. The recovery program should be started as early as possible, and should be indicated immediately after immobilization, to prevent complications [1,4,6,12]. Throughout this study, we considered the implementation of the proposed objectives from the beginning and also verification of the hypothesis from which we started. In order for the physiotherapy program to be carried out in optimal conditions, we followed a series of principles.